1990
DOI: 10.1038/bjc.1990.94
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that multiple myeloma may be regulated by homeostatic control mechanisms: correlation of changes in the number of clonogenic myeloma cells in vitro with clinical response

Abstract: Myeloma colonies (MY-CFUc) could be grown in vitro for 6 months (median time) after a group of 12 myeloma patients had reached complete remission (CR). In a second group of 25 patients MY-CFUc increased in 17/25 and GM-CFUc in 20/25 patients after cyclophosphamide even though 24/25 patients had a partial response to VAMP and one was in CR. These data suggest that cell killing by cyclophosphamide stimulates residual tumour cells into proliferation and adds further support to the idea that myeloma is under some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…5 Preclinical data suggest that cyclophosphamide may enhance the efficacy of VAD-based chemotherapeutic regimens. 6 Furthermore, clinical data indicate that cyclophosphamide, especially in intermediate to higher dose levels, is effective in melphalan-resistant disease. 7,8 We have therefore conducted a phase II trial evaluating the safety and efficacy of non-infusional vincristine and epirubicin in addition to cyclophosphamide and high-dose dexamethasone as induction and salvage treatment in multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…5 Preclinical data suggest that cyclophosphamide may enhance the efficacy of VAD-based chemotherapeutic regimens. 6 Furthermore, clinical data indicate that cyclophosphamide, especially in intermediate to higher dose levels, is effective in melphalan-resistant disease. 7,8 We have therefore conducted a phase II trial evaluating the safety and efficacy of non-infusional vincristine and epirubicin in addition to cyclophosphamide and high-dose dexamethasone as induction and salvage treatment in multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…Data from our laboratory have shown that a priming dose of cyclophosphamide given 7 d before high-dose melphalan (Maitland et al, 1990) or VAMP increased the clonogenecity of myeloma cells and subsequent cell kill. Thus cyclophosphamide was added to the regimen (C-VAMP) with the aim of activating tumour cells into cycle and therefore rendering them more susceptible to VAMP, although we also expected to obtain a direct effect on tumour cell kill from cyclophosphamide itself.…”
mentioning
confidence: 99%
“…Over the past two to three years we have investigated, in multiple myeloma patients, the relationship between types of clinical treatment and the growth of clonogenic myeloma cells (MY-CFUJ from bone marrow aspirates using an in vitro assay (Millar et af., 1988(Millar et af., , 1989Bell et af., 1988;Maitland et al, 1990). The first study involved patients receiving the drug combination vincristine, adriamycin and methyl prednisolone (VAMP) repeated every 21 days to maximum response followed by high dose melphalan at 140 mg/m2 or 200 mg/m2 with autologous bone marrow transplantation (Gore et af., 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Data from our laboratory have shown that a 'priming' dose of cyclophosphamide (Millar and McElwain, 1978) (500 mg i.v. bolus) which is given to patients 7 days before high dose melphalan increases the clonogenicity of myeloma cells in vitro in approximately 68 per cent of patients (Maitland et al, 1990). The rationale for adding cyclophosphamide on days 1, 8 and 15 of the treatment was that activation of tumour cells into cycle might render them more susceptible to the toxic effects of VAMP as well as cyclophosphamide itself.…”
Section: Introductionmentioning
confidence: 99%